2019
DOI: 10.22469/jkslp.2019.30.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Study for Correlation between Objective and Subjective Voice Parameters in Patients with Dysphonia

Abstract: Background and Objectives Voice evaluation is classified into subjective tests such as auditory perception and self-measurement, and objective tests such as acoustic and aerodynamic analysis. When evaluating dysphonia, subjective and objective test results do not always match. The purpose of this study was to analyze the relationship between subjective and objective evaluation in patients with dysphonia and to identify meaningful parameters by disease. Materials and MethodThe total of 322 patients who visited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Bhuta et al [ 17 ] found relationships between the voice turbulence index (VTI) and G, NHR with G and R, and soft phonation index (SPI) with G and B. These results were confirmed in more recent papers of Park et al [ 41 ] and Narisimhan et al [ 42 ]. Focusing on SD, Dejonckere et al [ 43 ] found relationships only between B and devoicing measures extracted with AMPEX: PVF (i.e., the proportion of voiced frames), PVS (i.e., the proportion of speech frames), and VL90 (which represents the 90th percentile of the voicing length distribution).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Bhuta et al [ 17 ] found relationships between the voice turbulence index (VTI) and G, NHR with G and R, and soft phonation index (SPI) with G and B. These results were confirmed in more recent papers of Park et al [ 41 ] and Narisimhan et al [ 42 ]. Focusing on SD, Dejonckere et al [ 43 ] found relationships only between B and devoicing measures extracted with AMPEX: PVF (i.e., the proportion of voiced frames), PVS (i.e., the proportion of speech frames), and VL90 (which represents the 90th percentile of the voicing length distribution).…”
Section: Discussionmentioning
confidence: 62%
“…In 25% of observations, NNE, a measure of noise alternative to HNR, was considered relevant, but its total contribution weight was equal to 2.4% only. However, it is important to specify that these discrepancies with literature results [ 39 , 41 , 42 ] are probably caused by different tasks: while jitter and NNE typically show strong correlations with R when healthy subjects are compared with patients diagnosed with AdSD, probably jitter and NNE do not represent relevant parameters to assess and distinguish among different AdSD severity classes. B ratings and F1 median values showed the strongest relationship.…”
Section: Discussionmentioning
confidence: 85%